(untitled) (Community Based Medical Journal, 2023)
A descriptive, comparative study was conducted in the Department of Conservative Dentistry and Endodontics, Dhaka Dental College Hospital, Bangladesh, from December 2014 to November 2015, to evaluate the effectiveness of calcium hydroxide as a root canal sealer constituent. A total of 60 patients were selected by purposive sampling technique. Patients were divided into two equal groups of 30: group-I had zinc-oxide eugenol [ZOE] cement as a root canal sealer, while group-II had calcium hydroxideor sealapex [Ca(OH)2] cement as a root canal sealer. Total number of teeth treated by single-visit root canal therapy. Out of 60 patients, 37(61.7%) patients were male. In ZOE group, the highest incidence was in age group 21-30 years, where as in Ca(OH)2 group, it was in 11-20 years. The mean age of the patients was 27.62±6.20 years in ZOE group and 25.0±6.14 years in Ca(OH)2 group. 21(70.0%) mentioned trauma as an etiological factor followed by caries 4(13.33%) in ZOE group, while 18(60.0%) patients mentioned trauma followed by caries 6(20.0%) in Ca(OH)2 group. In ZOE group, the incidence of pain was 23(76.67%), and in Ca(OH)2 group, 22(73.33%) reported pain. Periapical radiolucency follow-up findings were significantly better at 3-month and 6-month follow-ups in the Ca(OH)2 group. The difference inthe final outcome of effectiveness in both ZOE and Ca(OH)2 group in the management of periradicular pathosis was statistically not significant (P>0.05). The present study findings revealed that single-visit root canal therapy was equally effective in the management of endodontically involved teeth with periradicular pathosis. After 12 months, in follow-up with post-operative clinical and radiological evaluations, Ca(OH)2 sealer group showed better results than ZOE sealer group. However, in shorter follow-ups, Ca(OH)2 sealer group showed significantly better findings as compared to ZOE sealer groups. CBMJ 2023 July: vol. 12 no. 02 P: 141-149